Antifungal activity of azole compounds CPA18 and CPA109 against azole-susceptible and -resistant strains of Candida albicans - Andrew Warrilow (Journal of Antimicrobial Chemotherapy, 2013)
AbstractOBJECTIVES: In this study we investigated the in vitro fungistatic and fungicidal activities of CPA18 and CPA109, two azole compounds with original structural features, alone and in combination with fluconazole against fluconazole-susceptible and -resistant Candida albicans strains.METHODS: Antifungal activities were measured by MIC evaluation and time-kill studies. Azole binding analysis was performed by UV-Vis spectroscopy. Hyphal growth inhibition and filipin and propidium iodide staining assays were used for morphological analysis. An analysis of membrane lipids was also performed to gauge alterations in membrane composition and integrity. Synergism was calculated using fractional inhibitory concentration indices (FICIs). Evaluation of cytotoxicity towards murine macrophages was performed to verify selective antifungal activity.RESULTS: Even though their binding affinity to C. albicans Erg11p is comparable to that of fluconazole, CPA compounds are active against resistant strains of C. albicans with a mutation in ERG11 sequences and/or overexpressing the ABC transporter genes CDR1 and CDR2, which encode ATP-dependent efflux pumps. Moreover, CPA18 is fungistatic, even against the two resistant strains, and was found to be synergistic with fluconazole. Differently from fluconazole and other related azoles, CPA compounds induced marked changes in membrane permeability and dramatic alterations in membrane lipid composition.CONCLUSIONS: Our outcomes suggest that CPA compounds are able to overcome major mechanisms of resistance in C. albicans. Also, they are promising candidates for combination treatment that could reduce the toxicity caused by high fluconazole doses, particularly in immunocompromised patients.